The wedding song in Greek literature and culture - Badnall, Toni Patricia (2009)
This thesis examines the Greek wedding song and its function in literature and culture. The genre, hymenaios or epithalamium, has received little scholarly attention, particularly in English (cf. Muth, WS 1954; Tufte, Los Angeles 1970; Contiades-Tsitsoni, Stuttgart 1990, ZPE 1994; Swift, JHS 2006 & DPhil diss.). Yet an examination of the poetry of marriage, a crucial aspect in the study of the ancient world, contributes to our understanding of gender and social relations, as well as literature.